ANALISIS FAKTOR BUDAYA ORGANISASI YANG MEMPENGARUHI PERUBAHAN BUDAYA KEARAH PELAYANANYANG BERPUSAT PADA PASIEN (PATIENT CENTERED CARE) DI RSUD DR. M.M. DUNDA LIMBOTO KABUPATEN GORONTALO - Fitria Handayani (-, 2021)
Patient centered care is an innovative approaches to the planning, delivery, and evaluation of health services based on mutually beneficial partnerships between health care givers, patients, and families. Patient centered care is one of the Organization’s  members that behavior is influenced by the culture of the organization. The purpose of this research is to analyze the factors which influence the culture of the Organization patient centered care in the Dr. M. M. Dunda Limboto hospital (RSUD Dr. M. M. Dunda Limboto). This type of research is analytic survey with cross sectional approach that uses the chi square test on 70 people nurses. The results showed there is a relationship between communication, training, decision making, risk taking, reward, and cooperation with patient centered care (p = 0.001-0.039). The most dominant variables related to patient centered careare the communication. So nurses communication needs to be improved for a change of culture at Dr. M. M. Dunda Limboto Hospital (RSUD Dr. M. M. Limboto).